Model of pedagogical accompaniment from a socio-critical reflective perspective for teaching performance in pre-professional practice, Abancay 2024 - Arredondo, Jose Luis Angelo; Vera, Juan Raul Egoavil; Mejia, Percy Junior Castro (Edelweiss Applied Science and Technology, 2024)
This research suggests a model of pedagogical accompaniment based on a reflective socio-critical perspective to optimize teaching performance in pre-professional practice. Through a quantitative approach and a non-experimental cross-sectional design, the opinions of 92 teachers from Abancay were analyzed using structured questionnaires. The results showed that pedagog-ical accompaniment positively influences teachers’ professional development, promoting critical and reflective competencies. However, no significant correlations were found between the fre-quency and quality of accompaniment and teaching performance, indicating that the effective-ness of the model depends more on its comprehensive and contextualized implementation than on these individual factors. The study highlights Paulo Freire’s method, which emphasizes criti-cal reflection and empowerment as fundamental bases of education. It also stresses the need for continuous pedagogical support that addresses socio-emotional and pedagogical aspects to face the challenges of teaching practice. It concludes that a flexible model tailored to the specific de-mands of teachers is essential to enhance the impact of pedagogical accompaniment, ensuring independent and sustainable professional development.